Tanggung Jawab Penanganan Kebakaran Hutan : Studi Kasus di Kabupaten Kotawaringin Timur Tahun 2023 - Dilla, Amanda Aspasia; Ramdani , Rijal (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2024)
East Kotawaringin District in Central Kalimantan Province faces recurring forest and land fires with severe environmental and social consequences. To address this, the Central Kalimantan Provincial Government delegated fire management responsibilities to local agencies in East Kotawaringin through the Regional Regulation of Central Kalimantan Province No. 1 of 2020. This study aims to evaluate the process of responsibility transfer and its implementation in disaster management using qualitative methods, including document analysis, interviews with local officials, and case studies of 2023 fire incidents. The findings indicate that the regulation has well-structured the transfer of responsibilities, enabling a more localized response. However, significant challenges persist, such as limited training for field officers, inadequate budget allocations, and insufficient infrastructure and logistics. The study highlights the importance of provincial support and stakeholder collaboration in addressing these challenges. Strengthening training, funding, and infrastructure is essential to optimize fire control efforts in East Kotawaringin District moving forward.